2009
DOI: 10.1158/1078-0432.ccr-08-1656
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB-Mediated Transforming Growth Factor-β-Induced Expression of Vimentin Is an Independent Predictor of Biochemical Recurrence after Radical Prostatectomy

Abstract: Purpose: Transforming growth factor-β (TGF-β)-mediated epithelial-to-mesenchymal transition (EMT) has been shown to occur in some cancers; however, the pathway remains controversial and varies with different cancers. In addition, the mechanisms by which TGF-β and the EMT contribute to prostate cancer recurrence are largely unknown. In this study, we elucidated TGF-β-mediated EMT as a predictor of disease recurrence after therapy for prostate cancer, which has not been reported before. Experimental Design: We a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
106
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 32 publications
5
106
0
Order By: Relevance
“…These data are in concordance with our results showing an increased expression in treated tumors of NF-kB subunits and NF-kB-regulated cytokines, such as IL-6, adding support to a body of evidence on the involvement of this pathway in resistance to chemotherapy in prostate cancer (11). On the other hand, NF-kB activation may induce EMT in prostate cancer (34). Although our study did not investigate the potential causal relationship between NF-kB activation and EMT, this last phenomenon was found to be highly relevant in resistance to therapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data are in concordance with our results showing an increased expression in treated tumors of NF-kB subunits and NF-kB-regulated cytokines, such as IL-6, adding support to a body of evidence on the involvement of this pathway in resistance to chemotherapy in prostate cancer (11). On the other hand, NF-kB activation may induce EMT in prostate cancer (34). Although our study did not investigate the potential causal relationship between NF-kB activation and EMT, this last phenomenon was found to be highly relevant in resistance to therapy.…”
Section: Discussionsupporting
confidence: 93%
“…CD44 and VIM expression in primary tumors has been correlated with adverse prognosis (34,49). Notably, the few patients in our series with ZEB1 þ /CD44 þ tumor cells in primary tumors showed extremely aggressive clinical behavior.…”
Section: Discussionmentioning
confidence: 62%
“…A change in the cellular response to TGF-b is frequently observed in cancer, and there is great interest in the molecular mechanisms responsible for the switch of TGF-b signalling from tumor suppression to tumor promotion (Bierie and Moses, 2006;Inman, 2011). TGF-b1 inhibits proliferation of RWPE-1 cells and BPH-1 benign prostate epithelial cells (Ao et al, 2006), but does not affect proliferation of metastatic PC3 cells or transformed derivatives of BPH-1, where instead it promotes an epithelial-to-mesenchymal transition (Ao et al, 2006;Zhang et al, 2009). An important TGF-b target gene, PMEPA1, has been implicated in this TGF-b switch (Singha et al, 2010), and silencing of PMEPA1 has been shown to reduce RWPE-1 cell proliferation (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study revealed that JunB was a Smad1-responsive gene and that it was involved in suppression of prostate cancer metastasis (46). On the other hand, the role of NFB transcription factors has been well established in the development and progression of prostate cancer through its effect on apoptosis, invasion, and inflammation and particularly on androgen-independent and recurrent prostate cancer (47)(48)(49)(50). Therefore, ATF3 acts as a modulator of KAI1 transcription through coordinating other endogenous transcription factors as either co-activator or co-repressor, and this mechanism is dependent on the tumor stage and genetic background of tumors.…”
Section: Discussionmentioning
confidence: 99%